Down regulation of miR-30a-5p and miR-182–5p in gastric cancer: Clinical impact and survival analysis - Soliman, Shimaa E.; Elabd, Naglaa S.; EL-Kousy, Salah M.; Awad, Mohamed F. (Biochemistry and biophysics reports, 2021)
Gastric Cancer (GC) is a leading cause of morbidity and mortality worldwide, particularly in developing nations, only a few suitable gastric cancer serum biomarkers with acceptable sensitivity and specificity exist. This work aims to highlight and uncover miR-30a-5p and miR-182–5p′s diagnostic roles regarding gastric cancer and their roles in predicting prognosis. 148 patients participated in this study. Groups I, II, and III had 47 patients with GC, 54 patients with benign gastric lesions, and 47 apparently healthy subjects of coincided age and gender as controls, respectively. All participants were clinically evaluated and subjected to CBC, serum CEA, and CA19-9 by ELISA, and real-time PCR tests of miR-30a-5p and miR-182–5p. MiR30a-5p and miR-182–5p were down regulated in gastric cancer patients in Group I more than Groups II and III (P < 0.001). ROC curve analysis revealed that miR30a-5p had better AUC, sensitivity, and specificity (0.961%, 93.62%, and 90.74%respectively). When miR-182–5p was gathered with CEA and CA19-9, specificity raised to 98.15% and PPV to 97.6%. Lower miR-30a-5p levels are linked with the presence of distant metastases, advanced TNM stage, and degree of pathological differentiation of tumors in GC patients (p = 0.034, 0.019, 0.049) respectively. According to the multivariate analysis, miR30a-5p expression level could be an independent predictor of GC. Our results exhibited that miRNAs, miR-30a-5p and miR182–5p, gene expression have a diagnostic power and can identify patients with GC. MiR-30a-5p displayed the highest diagnostic specificity and sensitivity. Besides other known tumor markers, they could offer simple noninvasive biomarkers that predict gastric cancer. •Gastric Cancer (GC) proceeds to be a leading cause of morbidity and mortality worldwide, espcially in developing nations.•We observed that miR-30a-5P, miR-182–5 P showed considerably lower values in gastric cancer patients.•Lower miR-30a-5P level was significantly linked with distant metastases, advanced TNM stage and pathological differentiation of tumor.•Lower miR-30a-5P, and miR182–5 P gene expressions in gastric cancer patients were significantly associated with decreased PFS.•Lower miR-30a-5P expression level could be independent predictor for Gastric Cancer.